2011
DOI: 10.1021/jf2022836
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and Food Processing: From Semolina to Pasta

Abstract: The objective of this study was to investigate the metabolite variations during industrial pasta processing (from semolina to dried pasta) for five different commercial products. Up to 76 metabolites were detected. Significant differences were observed between wholemeal and refined pasta samples, with the wholemeal pasta richer in many classes of compounds such as phytosterols, policosanols, unsaturated fatty acids, amino acids, carotenoids, minerals, and so on. Significant differences were also observed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 52 publications
2
40
0
Order By: Relevance
“…The thermal resistance of carotenoids and tocols to the temperatures used during drying processes of wheat was also observed by Panfili et al (2005). A significant total carotenoid loss was observed during processing by Beleggia et al, 2011. Overall losses of carotenoids observed from semolina to pasta were between 55% and 80%.…”
Section: Impact Of Pasta-making Processes On the Content Of Tocols Cmentioning
confidence: 97%
“…The thermal resistance of carotenoids and tocols to the temperatures used during drying processes of wheat was also observed by Panfili et al (2005). A significant total carotenoid loss was observed during processing by Beleggia et al, 2011. Overall losses of carotenoids observed from semolina to pasta were between 55% and 80%.…”
Section: Impact Of Pasta-making Processes On the Content Of Tocols Cmentioning
confidence: 97%
“…For example, recent studies reported that organic cultivation was found to provide tomatoes with a significantly higher content of antioxidant phenolic compounds than conventional farming [33,35]. Finally, metabolomics allows scientists to discover and characterize the chemical modifications that result from food processing, which could significantly alter the molecular content and health properties of food [19,36,37]. The molecular composition of food products, indeed, can be significantly affected by different methods of food preparation (e.g., frying vs. baking, steaming vs. boiling) and preservation (freezing, drying, smoking, and refrigerating) [20,36,37].…”
Section: Food Metabolomementioning
confidence: 99%
“…Finally, metabolomics allows scientists to discover and characterize the chemical modifications that result from food processing, which could significantly alter the molecular content and health properties of food [19,36,37]. The molecular composition of food products, indeed, can be significantly affected by different methods of food preparation (e.g., frying vs. baking, steaming vs. boiling) and preservation (freezing, drying, smoking, and refrigerating) [20,36,37]. Recently, a metabolomics approach was used to determine the molecular difference between wholemeal and refined pasta samples, finding that the wholemeal pasta was richer in many classes of compounds such as phytosterols, policosanols, unsaturated fatty acids, amino acids, carotenoids, and minerals [36].…”
Section: Food Metabolomementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, with the high sensitivity and the selectivity of MS-based technologies, food constituents can be detected at trace levels (e.g., fmol). Composition analyses by MS-based metabolomics have been performed extensively for a large number of natural foods, including barley, potato cultivars, honey and olive oil [25][26][27][28], processed foods, such as ketchups, green tea and pasta [29][30][31][32], geneticallymodified crops, including transgenic potato, maize and soybean [15,[33][34][35], beverages, such as milk, wine and beer [36][37][38][39][40] and aquatic products, such as fish, shrimp, shark meat and mackerel [41,42]. Taking milk as an example, characterizing the composition, especially milk from different species, is important for uncovering the role of milk in food and health, as milk is the only bio-material to nourish and to sustain infant mammals.…”
Section: Metabolomics In the Characterization Of Food Compositionmentioning
confidence: 99%